Perioperative Healthcare Utilization of Patients Undergoing Brostrom Repair: A Truven Marketscan Retrospective Study - Michelle M. Coleman MD, PhD; Jenny Nguyen BSc; Megan Lameka MD; Sameh A. Labib MD (Foot & Ankle Orthopaedics)
Category: Ankle; Other Introduction/Purpose: Ankle sprains are one of the most common musculoskeletal injuries, and most will respond to nonoperative management. However, approximately 20% of patients will develop chronic ankle instability [CAI]. Surgical treatment of CAI is indicated when conservative treatment is not effective after three months with the Broström-Gould reconstruction being the gold standard. The healthcare utilization and costs of prolonged conservative treatment of operative musculoskeletal pathologies is understudied, so we aim to evaluate the patterns of healthcare utilization and estimated cost of care among patients who underwent Brostrom repair, contrasting those who sought surgical intervention earlier versus at later stages. This study could help demonstrate the economic burden placed on patients and the healthcare system with unnecessary prolonged nonoperative management of operative foot and ankle pathologies. Methods: MarketScan was queried for patients undergoing Brostrom Repair in both the inpatient and outpatient setting between January 2009 through December 2022 along with their corresponding nonsurgical encounters. ICD9/10 codes were used to identify patients with ankle instability as their primary diagnosis. Patients were then categorized into groups depending on the number of days between when they first presented for ankle instability and when they had a Brostrom Repair (within 1 month, 2-3 months, 3-6 months, 6 months-1 year, 1-2 years, and 2+ years). The number of patient encounters (which included physical therapy [PT], primary care visits, orthopedic visits, imaging, and corticosteroid injections ) was counted before and after surgery. Patients’ average number of encounters was calculated for each modality of visits. A two-sample t-test was used to compare the average usage before and after surgery (α = 0.05). Results: There was a total of 104,608 patient encounters (29.9% male, 70.1% female) with an average age of 35.9 +/- 14.9. Comparing average healthcare utilization before and after surgery, there was a significant decrease in patients undergoing surgery within 1 month. As the patient waits longer for surgery (1 month+), there is an upward trend of post-operative healthcare utilization. For patients that delayed surgery for 1 year or more, there was a significant increase in post-operative PCP visits, imaging, and consult visits. Cohorts that did not delay surgery for more than a year had a significant decrease post-operative imaging and PCP visits. For patients that delayed surgery for 1-3 months, patients had a significant decrease in almost all modalities (PCP visits, imaging, injections, and consults) post-operatively. Conclusion: This study evaluates the perioperative healthcare utilization of patients undergoing a Brostrom repair. Given that the average healthcare utilization of nonsurgical visits is significantly lower for the group who received surgery within 3 months of presenting with a diagnosis of ankle instability, there is merit for both the patient and the healthcare system for electing for an earlier surgery. This research opens the possibility of modeling the optimization of nonsurgical management to reduce overall healthcare utilization and thus costs.